TOPOGRAPHIC CHANGES AFTER 2004 AND 2005 EARTHQUAKES AT SIMEULUE AND NIAS ISLANDS IDENTIFIED USING UPLIFTED REEFS - S. Suyarso (JOURNAL OF COASTAL DEVELOPMENT, 2008)
Research on the topographic changes due to Aceh earthquake, December 2004 and Nias earthquake, March 2005 was carried out at Weh, Simeulue and Nias islands from end of July until August 2005. The topographic changes were measured based on the present position of uplifted coral reefs with geodetic methods. Research results shows northwest part of Simeulue Island uplifted 1.55 up to 1.60 meters after earthquake on December 2004 and three months later southeast part of Simeulue Island and northwest part of Nias Island uplifted 1.70 up to 2.70 meters due to earthquake on March 2005. The raised shallow water reef flats become new land and apart of previously shallowest reef slope become new reef flats.